A General Method For Evaluating Outage Probabilities Using Padé Approximations - Stokes, Jay; Ritcey, James A. (IEEE Global Telecommunications Conference (GLOBECOM), 1998)
Many diﬀerent methods have been derived for evaluating the outage probability given fading, shadowing, or a combination of fading and shadowing. However, each of these methods imposes restrictions on the parameters or combination of fading and shadowing distributions. In this paper, we develop a general method to evaluate outage probabilities without restrictions based on Pade approximations (PAs). Results show that imposing restrictions on the channel model, such as the Ricean specular parameter, can lead to large errors in the outage probability. The PA method is applicable to both the forward link and the reverse link and is extremely eﬃcient due to the use of residues or saddle point integration. Pade approximations allow the use of any fading or shadowing models given the moments of each distribution. In addition, this new method includes the eﬀects of complex AWGN. For pico cellular environments operating at low values of carrier SNR, we show that the noise provides a signiﬁcant contribution to the outage probability.